Anaerobic bacteria cultured from cystic fibrosis airways correlate to milder disease: a multisite study. Issue 1 (12th July 2018) - Muhlebach, Marianne S.; Hatch, Joseph E.; Einarsson, Gisli G.; McGrath, Stef J.; Gilipin, Deirdre F.; Lavelle, Gillian; Mirkovic, Bojana; Murray, Michelle A.; McNally, Paul; Gotman, Nathan; Davis Thomas, Sonia; Wolfgang, Matthew C.; et al.
Anaerobic and aerobic bacteria were quantitated in respiratory samples across three cystic fibrosis (CF) centres using extended culture methods. Subjects aged 1–69 years who were clinically stable provided sputum (n=200) or bronchoalveolar lavage (n=55). 18 anaerobic and 39 aerobic genera were cultured from 59% and 95% of samples, respectively; 16 out of 57 genera had a ≥5% prevalence across centres. Analyses of microbial communities using co-occurrence networks in sputum samples showed groupings of oral, including anaerobic, bacteria, whereas typical CF pathogens formed distinct entities. Pseudomonas was associated with worse nutrition and F508del genotype, whereas anaerobe prevalence was positively associated with pancreatic sufficiency, better nutrition and better lung function. A higher total anaerobe/total aerobe CFU ratio was associated with pancreatic sufficiency and better nutrition. Subjects grouped by factor analysis who had relative dominance of anaerobes over aerobes had milder disease compared with a Pseudomonas -dominated group with similar proportions of subjects that were homozygous for F508del. In summary, anaerobic bacteria occurred at an early age. In sputum-producing subjects anaerobic bacteria were associated with milder disease, suggesting that targeted eradication of anaerobes may not be warranted in sputum-producing CF subjects. Anaerobic bacteria are cultured across all ages, occur as communities and correlate with milder CF disease in adults http://ow.ly/7wQ430khMmE